2003
DOI: 10.1038/nbt824
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus in mice by RNA interference

Abstract: Hepatitis B virus (HBV) infection substantially increases the risk of chronic liver disease and hepatocellular carcinoma in humans. RNA interference (RNAi) of virus-specific genes has emerged as a potential antiviral mechanism. Here we show that RNAi can be applied to inhibit production of HBV replicative intermediates in cell culture and in immunocompetent and immunodeficient mice transfected with an HBV plasmid. Cotransfection with plasmids expressing short hairpin RNAs (shRNAs) homologous to HBV mRNAs induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
412
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(427 citation statements)
references
References 22 publications
11
412
0
4
Order By: Relevance
“…Several reports, including the accompanying report by Tompkins et al (41), have shown that rapid injections of a large volume of siRNA in PBS i.v. can deliver siRNA to the lungs (and other organs) (22)(23)(24)(25). Our findings demonstrate that conventional i.v.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Several reports, including the accompanying report by Tompkins et al (41), have shown that rapid injections of a large volume of siRNA in PBS i.v. can deliver siRNA to the lungs (and other organs) (22)(23)(24)(25). Our findings demonstrate that conventional i.v.…”
Section: Discussionmentioning
confidence: 55%
“…To date, the most effective siRNA delivery in mice relies on rapid i.v. injection of a large volume of siRNA solution (hydrodynamic or high-pressure transfection) (22)(23)(24)(25). However, this traumatic procedure is unlikely to be practical in humans.…”
mentioning
confidence: 99%
“…This stringent approach (injection within a few seconds in the tail vein of a volume onetenth the mass of the animal) appears to bring siRNA (and DNA) delivery mainly targeted to the liver. [9][10][11][12][13] Other methods were described where a systemic or a localized (portal vein injection) delivery was obtained by adding different chemical compounds to the siRNA solution. [14][15][16][17] siRNA gene silencing could be obtained in vivo on reporter as well as endogenous genes.…”
Section: Introductionmentioning
confidence: 99%
“…In HBV studies, several investigators demonstrated that HBV gene expression and replication by HBV plasmids, which were delivered to the mouse liver by hydrodynamic injection, were suppressed by coinjection of synthetic siRNAs or plasmid vectors that express small hairpin RNAs (shRNAs). [15][16][17] Furthermore, the in vivo anti-HBV effect of siRNAs can be further enhanced by chemical modification and lipid-encapsulation of siRNAs. 18,19 However, due to their short half-life and low in vivo transfection efficiency, synthetic siRNAs and plasmid vector-based shRNAs are unlikely to be effective in treating chronic HBV infection, because virtually all hepatocytes in these patients are infected.…”
Section: Introductionmentioning
confidence: 99%